Climate change and the role of universities: the potential of land-based teacher education and agroecology: THE POTENTIAL OF LAND-BASED TEACHER EDUCATION AND AGROECOLOGY - Hage, Salomão Mufarrej; Castagna Molina, Mônica; McCowan, Tristan (Revista Brasileira de Política e Administração da Educação - Periódico científico editado pela ANPAE, 2022)
This article provides a critical reflection on climate change in contemporary times, addressing the responses made by universities through land-based teacher education courses with a agroecology approach. It draws on historical dialectical materialism, with reference to land-based higher education and the Transforming Universities for a Changing Climate project. Significant possibilities are identified for the critical development of educators with an understanding of agroecology linked to the material production of life in the farming territories.